JURNAL IMPLEMENTASI KEBIJAKAN PENDIDIKAN KARAKTER PADA ANAK USIA DINI DI TK NEGERI 2 YOGYAKARTA - Citra, Rizka Pradini (Spektrum Analisis Kebijakan Pendidikan, 2023)
This study aims to describe the implementation, supporting factors, and inhibiting factors for the implementation of character education policies in early childhood at TK Negeri 2 Yogyakata. This study uses the theory of policy implementation from Edward III's theory. This type of research is descriptive with a qualitative approach. Data collection techniques using observation, interviews, and documentation studies. The data analysis technique uses the Miles, Huberman, and Saldana models, namely data collection, data condensation, data presentation, and drawing conclusions. This study uses a triangulation technique to test the validity of the data. The results of this study indicate that the implementation of character education policies in early childhood in TK Negeri 2 Yogyakarta: (a) Communication between implementers (b) Availability of resources in the form of human resources, funding sources, as well as facilities and infrastructure (c) Disposition of the executors (d) Bureaucratic structure (e) Supporting factors, namely teacher commitment, funding sources, and school facilities (f) Inhibiting factors, namely resources and environmental factors.Keywords: Implementation, supporting factors, inhibiting factors, character education in early childhood